Evidence Based Practice Nursing Research Conference is Sept. 27 - Uribes, Tom::::::::: (2013)
The fall 2013 Evidence Based Practice Nursing Research Conference will be 8 a.m. to 1 p.m. Friday,Sept. 27, at the Saint Agnes Conference Center, North Tower.